Biofabrication of ZnS:Mn luminescent nanocrystals using histidine, hexahistidine, and His-tagged proteins: a comparison study - Zhou, Weibin (2014)
The ubiquitous hexahistidine purification tag has been used to conjugate proteins to the shell of CdSe:ZnS quantum dots (QDs) due to its affinity for surface-exposed Zn(2+) ions but little attention has been paid to the potential of His-tagged proteins for mineralizing luminescent ZnS nanocrystals. Here, we compare the ability of free histidine, a His tag peptide, His-tagged thioredoxin (TrxA, a monomeric protein), and N- and C-terminally His-tagged versions of Hsp31 (a homodimeric protein) to support the synthesis of Mn-doped ZnS nanocrystals from aqueous precursors under mild conditions of pH (8.2) and temperature (37°C). We find that: (1) it is possible to produce poor quality QDs when histidine is used at high (8 mM) concentration; (2) an increase in local histidine concentration through repetition of the amino acid as a His tag decreases the amount of needed reagent ≈10-fold and improves optical properties; (3) fusion of the same His tag to TrxA allows for ZnS:Mn QDs mineralization at micromolar concentrations; and (4) doubling the local hexahistidine concentration by exploiting Hsp31 dimerization further improves nanocrystal luminescence with the brightest particles obtained when His tags are spatially co-localized at the Hsp31 N-termini. Although hexahistidine tracts are not as efficient as combinatorially selected ZnS binding peptides at QD synthesis, it should be possible to use the large number of available His-tagged proteins and the synthesis approach described herein to produce luminescent nanoparticles whose protein shell carries a broad range of functions.